Pengaruh Kepemimpinan Kepala Koordinator Wilayah Terhadap Disiplin Kerja Tenaga Administrasi - Fawziyah, Reza; Fatihah, Imroatul; Santoso, Sigit (IAIN Syekh Nurjati Cirebon, 2020)
Achievement of educational goals is seen from the role of leadership and work discipline of the administrative staff. The facts in the field of leadership carried out by the head of the regional coordinator at the Regional Coordinator for Education in the Sumber District, Cirebon Regency, have not been going well so that it will have an impact on the work discipline of administrative personnel. This study aims to determine the effect of the leadership of the regional coordinator on the work discipline of administrative personnel in the Regional Coordinator for Education, Gempol District, Cirebon Regency. The method used is descriptive quantitative. Data collection techniques using questionnaires, observation and documentation. The technical data analysis used descriptive analysis and the chi square test. Based on the results of the questionnaire calculation at the KORWIL for Education, Gempol District, Cirebon Regency, that: 1) The Leadership of the Regional Coordinator for Education, Gempol District, Cirebon Regency is very strong, 2) The Work Discipline of Administrative Personnel at KORWIL in the Education Sector, Gempol District, Cirebon Regency is very strong, 3 ) It was found that there was an influence between the leadership of the regional coordinator on the work discipline of administrative personnel in the Regional Coordinator for Education, Gempol District, Cirebon Regency, which was classified as positively related to the good category.Keywords: Leadership, Work Discipline, Administrative Personnel